2020
DOI: 10.18632/oncotarget.27431
|View full text |Cite
|
Sign up to set email alerts
|

The targeted LHRH analog AEZS-108 alters expression of genes related to angiogenesis and development of metastasis in uveal melanoma

Abstract: Uveal melanoma (UM) is the most common malignant tumor of the eye. Recently, we have established that 46% of UM specimens express LHRH receptors. This finding supports the idea of a LHRH receptor-targeted therapy of UM patients. Cytotoxic analog of LHRH, AEZS-108 exhibits effective anti-cancer activity in LHRH-receptor positive cancers. AEZS-108 is a hybrid molecule, composed of a synthetic peptide carrier and the cytotoxic doxorubicin (DOX). In the present study, we investigated AEZS-108 induced cytotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…AEZS-108 is an analog of the Luteinizing Hormone-Releasing Hormone (LHRH) consisting of doxorubicin conjugated to a synthetic peptide containing LHRH that is used against cells expressing the LHRH-receptor. More importantly, the authors identified upregulation of MASPIN/SERPINB5, a tumor suppressor gene for UM [ 297 , 298 ], as well as downregulation of proteins related to angiogenesis, such as HIF-1α and VEGF, as cause of AEZS-108 efficacy [ 299 ]. Given to the pivotal role of angiogenesis in the metastatization of UM [ 195 ], the regulation of HIF-1α /VEGF axis by AEZS-108 is of particular relevance.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…AEZS-108 is an analog of the Luteinizing Hormone-Releasing Hormone (LHRH) consisting of doxorubicin conjugated to a synthetic peptide containing LHRH that is used against cells expressing the LHRH-receptor. More importantly, the authors identified upregulation of MASPIN/SERPINB5, a tumor suppressor gene for UM [ 297 , 298 ], as well as downregulation of proteins related to angiogenesis, such as HIF-1α and VEGF, as cause of AEZS-108 efficacy [ 299 ]. Given to the pivotal role of angiogenesis in the metastatization of UM [ 195 ], the regulation of HIF-1α /VEGF axis by AEZS-108 is of particular relevance.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…Recent research has sought to further evaluate the presence of LHRH and the effects of cytotoxic LHRH analogs – such as AEZS-108 and AN-207 – on cell lines [28-30]. Unfortunately, problematic cell lines (including OCM3 and OCM1), originally thought to be derived from UM tumors but later shown to be of skin melanoma origin, were used, limiting their applicability to UM (Table 4) [31-37].…”
Section: Evidence For Sex Hormone Receptor Expression In Nevi/um Tumorsmentioning
confidence: 99%
“…However, since UM primary tumors were also found to express LHRH, further work to validate the findings in confirmed UM cell lines with GNAQ/GNA11 mutations should be done. AEZS-108, a chemotherapy drug which consists of [D-Lys6]-LHRH linked to 1 molecule of doxorubicin (DOX), significantly reduced OCM3 cell viability by 36.3% after 24 h and by 84.7% after 48 h. AEZS-108 may prevent ECM degradation, angiogenesis, and migration of tumor cells via the regulation of MASPIN, HIF1A, and their target genes [28, 30]. These LHRH analogs are discussed further in detail in the section Sex Hormones as Potential Targets for Therapy in UM.…”
Section: Evidence For Sex Hormone Receptor Expression In Nevi/um Tumorsmentioning
confidence: 99%
“…It is expected that, by binding to its receptor, the GnRH derivative may specifically carry the cytotoxic drug to cancer cells without affecting normal cells. AEZS-108 (also known as AN-152), a bioconjugate consisting of a GnRH derivative covalently linked to doxorubicin via an ester bond, was developed, and its anticancer activity was investigated in different types of tumors [ 282 , 283 , 284 ]. This peptide cytotoxin was reported to exert a significant antiproliferative/proapoptotic activity in PCa, and specifically in CRPC cells, in vitro and in preclinical studies [ 285 , 286 , 287 ].…”
Section: Androgen and Gonadotropin-releasing Hormone Receptors: Molecular Targets For Therapeutic Strategies In Crpcmentioning
confidence: 99%